Dinamika Spasial Abrasi dan Akresi Menggunakan Digital Shoreline Analysis System (DSAS) Berbasis Citra Sentinel-2 untuk Mendukung Pengelolaan Wilayah Pesisir Berkelanjutan di Estuari Sungai Batakan - Gerarda Anastasya Bisa; Efrinda Ari Ayuningtyas; Wisnu Putra Danarto; Indra Agung Pamuja (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2026)
Shoreline change is an important indicator for understanding coastal environmental dynamics as it reflects the interaction between erosion and accretion processes occurring both temporally and spatially. The Batakan River Estuary, located in Panyipatan District, Tanah Laut Regency, is a coastal area influenced by the interaction of fluvial and marine processes, making it vulnerable to shoreline morphological changes. This study aims to analyze shoreline dynamics in the Batakan River Estuary during the 2020–2025 period using the Digital Shoreline Analysis System (DSAS) approach. The data consisted of shorelines extracted from Sentinel-2 imagery acquired between 2020 and 2025 and processed using Google Earth Engine. The analysis employed the Net Shoreline Movement (NSM) parameter to measure shoreline displacement and the End Point Rate (EPR) parameter to calculate the annual rate of shoreline change. The results indicate that shoreline changes occurred throughout the estuarine area, with distinct characteristics in each segment. Segment 1 was dominated by accretion, with NSM values ranging from 0.70 to 167.06 m and EPR values ranging from 0.35 to 33.41 m/year. Segment 2 exhibited a fluctuating pattern, with NSM values ranging from -19.93 to 21.37 m and EPR values ranging from -3.99 to 4.27 m/year. Segment 3 experienced the highest erosion intensity, characterized by a minimum NSM value of -79.60 m and a minimum EPR value of -15.92 m/year. Meanwhile, Segment 4 showed a mixed pattern, with NSM values ranging from 10.71 to 57.55 m and EPR values ranging from -2.14 to 11.51 m/year. These findings indicate that shoreline dynamics in the Batakan River Estuary are spatially heterogeneous, forming distinct patterns across different segments of the estuary. The spatial information generated from this study can serve as a basis for coastal zone management, environmental monitoring, erosion mitigation planning, and sustainable sediment management.